Analisis Penerapan Standar Akuntansi Keuangan UMKM Budidaya Jamur Tiram Pada Kecamatan Rawas Ulu Sumatera Selatan - Akbar, Awal; Yudi, Yudi; Tiswiyanti, Wiwik (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This research aims to determine the application of Financial Accounting Standards for Accounting for Micro, Small and Medium Entities (SAK EMKM) in the UMKM for Cultivating Oyster Mushrooms in the Long River, Rawas Ulu District, Musi Rawas Ulu Regency. The background to this research is based on the fact that there are still many UMKM that have not prepared optimal financial reports based on SAK EMKM. Therefore, this research is important to identify the process of preparing financial reports and the factors that support or hinder the implementation of standards. This research uses a descriptive qualitative method which dominates the description and application of financial records based on SAK EMKM by conducting interviews and also taking financial reports for researchers to process so that they are appropriate based on SAK EMKM. The research results show that the process of preparing financial reports for UMKM is still carried out simply and is not completely in accordance with standards. The factors that cause the failure of SAK EMKM in the Long River Oyster Mushroom Cultivation business are internal factors, namely low understanding of accounting by business actors, discipline and human resources, while external factors are limited access and technology and supporting resources, lack of assistance and outreach from the government and institutions so that the implementation of SAK EMKM can run effectively.